Penerapan Metode DRILL untuk Meningkatkan Kemampuan Menulis Huruf A, I, U, E, O Siswa Kelas I/C (Tunagrahita) SDLBN 31 Pondok Duo Pariaman - Zulhemawati Zulhemawati (Jurnal Konseling dan Pendidikan, 2015)
Writing is one of important language skills which can help someone in delivering his opinion, feeling, and message. This research is aimed to increase students’ ability in writing letter a, i, u, e, o by applying drill method. Subject of this research are students grade I/C SDLBN 31 Pondok Duo Pariaman. This research consists of two cycles with 3 meetings for each cycle. Data of research were obtained through observation sheet and test. Researcher set the standard of succesfulness as 70%. After cycle I, got the students’ achievement percentage as 50%. Standard of students’ achievement percentage was achieved after the cycle II, it was 75%. Based on research result can be concluded that drill method in increasing students’ ability in wrting letter a, i, u, e, o.